Monetary policy under alternative exchange rate regimes in Central and Eastern Europe - Christina Ziegler (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
Monetary policy in CEE is an important determinant in the wage bargaining process, because trade unions have to predict inflation as one component of future real wages. This paper scrutinizes whether countries in CEE that officially announce an inflation target are tempted to act time-inconsistently and switch from the announced inflation target to an exchange rate target in order to sustain higher output via surprise inflation. If market participants discover the time-inconsistency, they will adjust their inflation expectations, which result in higher average rates of price increases. The time-inconsistent behavior in central bank interest rate setting is modeled by several Taylor rules. An empirical application provides evidence that some monetary authorities in CEE such as the Czech Republic and Slovakia have acted timeinconsistent and have focused on the exchange rate in periods of official inflation targeting, which might have contributed to higher average rates of inflation and welfare losses. Furthermore, uncertainty in wage determination process has risen due to a harder predictability of productivity and inflation as components of future nominal wages.
Keywords: E52; E58; F31; O52; P20; 330; monetary policy; Taylor rules; exchange rate regime; Central and Eastern Europe; inflation targeting; Geldpolitik; Zeitkonsistenz; Taylor-Regel; Inflation Targeting; Wechselkurssystem; Wirkungsanalyse; Inflation; Wohlfahrtseffekt; Ostmitteleuropa; Osteuropa